STRATEGI PENGEMBANGAN UMKM KULINER BERBASIS EKONOMI KREATIF DI KABUPATEN SAMPANG - Badrussoleh, Badrussoleh; Irawati, Anugrahini (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Businesses engaged in Micro, Small and Medium Enterprises (MSMEs) activities are one type that can grow and maintain the consistency of the national economy. Especially in the culinary industry, because culinary MSMEs require a solid development strategy, because they involve large and small elements. Therefore, culinary MSMEs must get attention by the Sampang Regency government and the business actors themselves so that the main issues raised discuss, to find out the obstacles faced by culinary MSME players in Sampang Regency, and to find out the development of creative economy-based culinary MSMEs in Sampang Regency. This research uses qualitative methods by conducting interviews and documentation. Because qualitative methods prioritize the process of in-depth communication contact between the researcher and the thing under study in order to understand a phenomenon in a natural social context. So that this research produces mandatory outputs containing research progress reports, final research reports, loog books of research activities, and posters as well as additional outputs in the form of scientific publications in accredited and unaccredited national journals.